Identification of an ARGONAUTE for Antiviral RNA Silencing in Nicotiana benthamiana(1)([C])([W])([OA]) - Scholthof, Herman B. (American Society of Plant Biologists, 2011)
ARGONAUTE proteins (AGOs) are known to be key components of the RNA silencing mechanism in eukaryotes that, among other functions, serves to protect against viral invaders. Higher plants encode at least 10 individual AGOs yet the role played by many in RNA silencing-related antiviral defense is largely unknown, except for reports that AGO1, AGO2, and AGO7 play an antiviral role in Arabidopsis (Arabidopsis thaliana). In the plant virus model host Nicotiana benthamiana, Tomato bushy stunt virus (TBSV) P19 suppressor mutants are very susceptible to RNA silencing. Here, we report that a N. benthamiana AGO (NbAGO) with similarity to Arabidopsis AGO2, is involved in antiviral defense against TBSV. The activity of this NbAGO2 is shown to be directly associated with anti-TBSV RNA silencing, while its inactivation does not influence silencing of transiently expressed transgenes. Thus, the role of NbAGO2 might be primarily for antiviral defense.